Intervensi Berkelanjutan Gizi Seimbang dan Aktivitas Fisik untuk Masyarakat Umum Selama Ramadhan - Bun Yurizali; Nurmaines Adhyka (Lembaga Pengembangan Kinerja Dosen, 2025)
Ramadan fasting often results in significant changes in diet, fluid intake, and daily physical activity levels. If not managed properly, these changes have the potential to negatively impact health, particularly in the elderly. This community service article aims to improve literacy and practice healthy lifestyles during and after Ramadan through educational intervention activities for retirees of PB Telkom Padang. The activity was held on Wednesday, February 26, 2025, starting at 08:00 WIB and ending, involving 80 participants. The intervention was carried out in two stages: educational counseling using PowerPoint media and distribution of leaflets as supporting introductory materials, followed by an interactive discussion between participants and the presenter. The leaflets functioned as an information retention tool, enabling participants to remember and apply the knowledge independently at home. In addition, providing souvenirs from sponsors to the most interactive participants increased motivation and active participation in the discussion session. The results of the activity showed an increase in participants' knowledge regarding the principles of balanced nutrition, the importance of hydration, and the choice of light physical activities appropriate to their physical condition during the fasting month. The participatory intervention method and receiving symbolic awards proved effective in fostering commitment to a healthy lifestyle. Based on these findings, similar interventions are recommended for implementation in other retirement communities, with additional quantitative evaluations to improve the accuracy of the impact and extend its benefits over the long term.